?-STATISTICAL BOUNDEDNESS FOR SEQUENCES OF FUZZY NUMBERS - Altinok, H.; Mursaleen, M. (Mathematical Soc Rep China, 2011)
In this article we introduce the notion of Delta-statistical boundedness for fuzzy real numbers and examine its some properties. We also give some relations related to this concept and construct some interesting examples.
Keywords: Fuzzy numbers; Statistical convergence; Statistical boundedness